Fingerprinting conflict: A comparative model with applications to archaeological and historical data - Søren Wichmann; Anna K. Loy; Anna-Theres Andersen; Ralf Bleile; Darja Jonjić; Jutta Kneisel; Norbert Nübler; Andrea Santamaria; Jens Schneeweiß; Gerald Schwedler; Katharina Zerzeropulos; Lorenz Kienle; et al. (PLoS ONE, 2025)
This paper is envisioned as a primarily methodological contribution towards a more sophisticated and systematic approach to conflict research in archaeology and history. Studies of conflicts in these fields have often focused on violence and war. Instead, we offer a more holistic approach to conflict research, taking into account different levels of both escalation and de-escalation that embrace all the possible aspects of a conflict from a mere undeveloped potential over complete annihilation to various countermeasures and stages of resolution. A model taking into account different levels of escalation and de-escalation is presented which embodies our multi-faceted view of conflicts and which also allows for a systematic, comparative analysis of conflict situations anywhere and any time in (pre)history. Through ten relatively detailed European case studies spanning the Bronze Age to the 20th century we demonstrate the comparative potential of our model and suggest ways in which it may help to identify typical patterns in conflict situations.